Topic: the scope of section 4(2) of the contracts act 1950 (revised 1974) / Balqis Aini Mohd Ali - Mohd Ali, Balqis Aini (Faculty of Law, 1985)
The purpose of this project paper is to discuss and to find the solution as to what extent does Section 4(2) of the Contracts Act, 1950 (Revised 1974) cover. This paper is intended to deal as to when the acceptance takes place as against the proposer and as against the acceptor in different forms of communication used i.e. post, telegram, telephone, telex, etc.